Clinical study of headache with special reference to ophthalmic cause - Shashi Jain,; Shivcharan Lal Chandravanshi1,; Laxmi Dukariya,; Eva Rani Tirkey,; Sheel Chandra Jain, (Universiti Kebangsaan Malaysia, 2015)
Background: Rapid modernization of the world requires more attention thereby aggravating eye strain in individuals, resulting into various types of headache disorders. Headache-related disorders are an important cause of disability worldwide, and ophthalmic causes for headache are well known. Objectives: The aims of this study were: (i) to estimate the prevalence of headache disorders in patients attending the eye OPD; (ii) to evaluate the various causes of headache with special reference to ophthalmic conditions; and (iii ) to study the correlation between location of headache and possible ocular causes. Materials and Methods: A prospective study was carried out on 1520 patients from November 2006 to October 2009 at a tertiary eye care center. Detailed clinical history was taken with particular emphasis on onset, duration, location, intensity, character, diurnal variation, and exaggerating and relieving factors. Ocular examination included vision, slit-lamp examination, cycloplegic refraction, orthoptic evaluation, intraocular pressure measurement, and fundoscopy. Besides ocular examination, medical, ENT, dental, and neurological checkup along with investigations such as hemoglobin, blood sugar, X-ray of skull and paranasal sinuses, and CT scan of sinuses and brain were carried out whenever needed and treatment was advised accordingly. The data was entered on a Microsoft Excel spreadsheet and analyzed using SPSS software, version 14.0 (SPSS, Inc., Chicago, IL). P value o0.05 was considered statistically significant. Results: Our study included 1520 subjects complaining of headache. Maximum patients (47%) were in the age group of 16–30 years with female preponderance (56%). Ocular headache was found in 36% followed by primary headache (27%), ENT problems (17%), medical causes (12%), and miscellaneous causes (3%). Out of ocular causes of headache, refractive error (65%) was the most common cause followed by abnormalities of anterior part of eye (21%), muscles imbalance (18%), and posterior segment disorders (5%). Among various refractive errors, astigmatism was found in 41% cases, hypermetropia in 22%, and myopia in 12% patients. In our study, 64% cases were relieved of headache Conclusion: Headache is multifactorial in origin. Possibility of ocular causes should be kept in mind during management of headache. An ophthalmologist may play a vital role in establishing the correct diagnosis of headache.